Mathematical modeling of wind power plants based on the Magnus effect - Tanasheva, N. K. (Nur-Sultan: publishing house "Altyn kitap", 2021)
The monograph is the first to obtain data on numerical modeling of wind power plants based on the Magnus effect with a different number of blades. The features of modeling turbulent flows around a cylindrical working element - a blade - are considered. Universal aerodynamic numerical dependencies of wind power plants were obtained by means of mathematical modeling, which were compared with experimental data obtained on prototypes. Designed for university students, teachers, undergraduates, PhD students in technical specialties and researchers.